Wawasan Al-Qur’an Tentang Teknologi: (Kajian Tafsir Maudhu’i) - Suhartawan, Budi; Hasanah, Muizzatul (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2023)
This paper aims to discuss Al-Qur'an Insights on Technology, a Thematic Interpretation (maudhu'i) study and can answer contemporary problems associated with the Al-Qur'an. This research is research based on literature (library research). The aim is to find evidence of the existence of Al-Qur'an Insights about technology in the Al-Qur'an. where this topic is a very interesting topic as material for scientific study in the style of scientific interpretation using the thematic interpretation method approach (maudu'i). is in the Al-Qur'an itself, including: First, Surah Hud verse 37, Second, Surah An-Nahl verse 14, Third, Surah Al Kahfi verse 96, Fourth, Surah Al Anbiya verses 79-80; Fifth, Surat Al-Anbiya verse 80 Sixth, Surat An-Naml verse 44, Seventh, Surat Saba verse 10, Eighth, Surat Ar Rahman verse 33, and Ninth, Surat Al Hadid verse 25.